The Training on Reputable International Journal Article Writing for Lecturers at Universitas Patompo - Abd. Rahim; Diah Retno Dwi Hastuti; Sri Astuty; Hastuty Mustakim; Erwin (LOSARI DIGITAL, 2026)
The low frequency of publication of articles in reputable international journals by lecturers in the Economics Education Study Program at Universitas Patompo, Makassar, is due to their limited ability to transform research findings into manuscripts that meet the standards of reputable international journals. The Community Service Program aims to increase the volume of lecturers' articles in reputable international journals to accelerate advancement to functional positions. Furthermore, this can improve the institution's reputation both nationally and internationally. The training results showed an increase in the proportion of 17 participants after the training or post-test assessment, which covered elements of understanding leading international journals, manuscript writing skills, and the publication process and language, with an average of 78.42%, compared to the pre-test average of only 56.85%. Accelerating publication in leading international journals can be achieved through institutional support, which includes funding incentives, writing support (article clinics), international research collaborations, and the application of Artificial Intelligence (AI) to increase research productivity.